2011
DOI: 10.2139/ssrn.3125314
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Risk-Taking in Pre-Crisis Investment Banks

Abstract: Efficiency and risktaking in precrisis investment banks Original CitationRadic, Nemanja, Fiordelisi, Franco and Girardone, Claudia (2011) Efficiency and risktaking in pre crisis investment banks. Working Paper. London Metropolitan University, London, UK.This version is available at http://eprints.hud.ac.uk/id/eprint/16670/ The University Repository is a digital collection of the research output of the University, available on Open Access. Copyright and Moral Rights for the items on this site are retained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Thus, the negative relationship between efficiency and z‐score implies that banks that have a lower level of efficiency have lower stability, indicating higher risk‐taking. This result is also consistent with Radić et al (2012) who argue that lower levels of efficiency with respect to costs and income causes banks to take higher risks, thus confirming the ‘bad management’ hypothesis identified in this article.…”
Section: Resultssupporting
confidence: 93%
“…Thus, the negative relationship between efficiency and z‐score implies that banks that have a lower level of efficiency have lower stability, indicating higher risk‐taking. This result is also consistent with Radić et al (2012) who argue that lower levels of efficiency with respect to costs and income causes banks to take higher risks, thus confirming the ‘bad management’ hypothesis identified in this article.…”
Section: Resultssupporting
confidence: 93%
“…In the banking literature, Bos et al (2009) identify these effects on efficiency levels and rankings when observed heterogeneity is omitted. In particular, in the case of risk exposure, Radić et al (2012) evaluate a sample of 800 investment banks of G-7 countries during the period 2001-2007 and find that omitting bank risk-taking from efficiency estimations leads to underestimating profit efficiency. The authors also find liquidity and capital risk exposures to be the most relevant factors determining cost and profit inefficiency.…”
Section: Heterogeneity and Risk In Bank Efficiency Measurementmentioning
confidence: 99%
“…Another widely used approach in the literature is to incorporate risk measures into frontier efficiency methods such as stochastic frontier analysis (SFA). Under this approach, Radić et al (2012) find capital and liquidity risk to have relevant effects on cost and profit efficiency of investment banks in G-7 countries. Also, Pessarossi and Weill (2014) find that increases of capital ratios during 2004-2009 had a positive influence on cost efficiency of Chinese banks, suggesting that capital requirements may improve cost efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The main distinctive element of their modeling framework is that accounting measures of risk and/or capital like the ones discussed above are incorporated into the production technology of banks to form the demand system for banking products. Many other empirical papers have followed this modeling choice henceforth (e.g., Radic et al, 2012). In our setting we borrow a number of elements from these studies, but we do not use specific variables to measure risk.…”
Section: Bank Risk Measurement and Empirical Factsmentioning
confidence: 99%